Design, Virtual Screening, Molecular Docking, ADME and Cytotoxicity Studies of 1,3,5-Triazine Containing Heterocyclic Scaffolds as Selective BRAF Monomeric, Homo and Heterodimeric Inhibitors - Singh, Ankit Kumar; Sreelakshmi, P.; Pathak, Prateek; Kumar, Adarsh; Singh, Harshwardhan; Yadav, Jagat Pal; Verma, Amita; Grishina, Maria; Kumar, Pradeep (Combinatorial Chemistry & High Throughput Screening, 2025)
Backgroundv-RAF murine sarcoma viral homolog B1 (BRAF) is one of the most frequently mutated kinases in human cancers. BRAF exhibits three classes of mutations: Class I monomeric mutants (BRAFV600), class II BRAF homodimer mutants (non-V600), and class III BRAF heterodimers (non-V600).MethodsIn this paper, the protein-ligand interaction site of all three mutants: BRAF monomer, BRAF homodimer BRAF2:14-3-32, and BRAF heterodimer BRAF:14-3-32:MEK (Mitogen extracellular Kinase) has been discussed. FDA-approved drugs still have limitations against all three classes of mutants, especially against the second and third classes. Using the DesPot grid model, 1114 new compounds were designed. Using virtual screening, the three PDB Ids 4XV2 for monomers, 7MFF for homodimers, and 4MNE for heterodimers were used for 1114 newly designed compounds.ResultsDabrafenib, encorafenib, sorafenib and vemurafenib were included as standard drugs. The top 10 hit molecules were identified for each protein. Additional binding studies were performed using molecular docking studies on the protein-ligand site of each PDB identifier. Absorption, distribution, metabolism, excretion (ADME) and toxicity studies were also performed.ConclusionIt was identified that top-hit molecules had better binding and interaction activity than standard in all three classes of mutants.
Keywords: cytotoxicity